Enhancing professionalism of prospective accounting teachers in the era of merdeka curriculum - Hanjar Ikrima Nanda; Sheila Febriani Putri; Nadia Arli Rafifah; Gina Oktavia (Universitas Muhammadiyah Magelang, 2023)
The merdeka curriculum system is still relatively new in the realm of education, so its implementation cannot yet be fully understood. The aim of this community service is to enhance the professionalism and skills of prospective accounting teachers in developing teaching modules based on the merdeka curriculum, better preparing them for the Accounting Vocational School environment. Participant selection was conducted openly, with 20 attendees, including students, alumni, and economics teachers. The program comprises three stages: focus group discussions, workshops and mentoring, and evaluation. Results from the program indicate that participants demonstrated an understanding of the merdeka curriculum at 91.43%, successfully composed teaching modules based on the merdeka curriculum at a rate of 81.43%, and expressed a confidence level of 81.86% in explaining the concept of the merdeka curriculum. This training resulted in products in the form of financial accounting and banking teaching modules. Additionally, evaluation results revealed that participants grasp the advantages and disadvantages of the created teaching modules.